Pengembangan E-LKPD Berbasis Problem Based Learning (PBL) dengan Aplikasi Liveworktsheet pada Materi Sistem Imunitas untuk Meningkatkan Kemampuan Berfikir Kritis Siswa SMA - Nayla Nayla; Syarifah Widya Ulfa (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
The research was conducted with the aim of developing an E-LKPD learning product based on Problem Based Learning (PBL) integrated with the Liveworksheet platform on the immune system material, as an effort to develop students' critical thinking skills, this research used the Research and Development (R&D) method by adapting the ADDIE model. The model consists of five main stages, namely analysis, design, development, implementation, and evaluation, which are carried out systematically to produce valid, practical, and effective learning products. The instruments used consisted of expert validation sheets, teacher and student response questionnaires, and problem-solving ability tests through pretest and posttest. The results of the study showed that the resulting E-LKPD product was classified as very valid with a validation score of 91%, had a very high level of practicality with a score of 90% from teachers and 94% from students, and showed high effectiveness with an N-Gain value of 0.76. In conclusion, E-LKPD based on Problem Based Learning (PBL) developed through Liveworksheet is suitable for use as a biology learning medium for the immune system material because it has been proven to be valid, practical, and effective in improving students' critical thinking skills. Keywords: Critical Thinking, E-LKPD, Liveworksheet, PBL, Immune System